(3GdeUGHjMs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi CTQa GdCfHjGA hGdeQSdjf(B...(3JegjO Gdabg dZI Gdage(B...s
(3BNQgG (B:s
...(3hHGdLedI abGdbhd HGdfUa djS HHYjO hEf cGf GdQHY gh GdCbQH, Je(B.s
(3hbY Ndd aj JQJjH GdUaMGJ aJbOeJ GdUaMI GdKGfjI Ydi GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B113s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B740s
(3gOjI GdYGQajf(B:(3L(B2(3,U(B351s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis